The Influence of Shared Participant Governance on the Integration of Service Networks: A Comparative Social Network Analysis. Issue 3 (2nd July 2016) - Raeymaeckers, Peter; Kenis, Patrick
ABSTRACT: We investigate how networks among service organizations are integrated through a shared participant type of governance. Shared participant governance is a non-brokered type of network coordination where a network is governed by its members without a separate governance entity. We study the integrative capacity of this type of governance by measuring the effect of participation in a shared participant governance on tie formation in networks among service organizations. We analyze three networks of service organizations in three districts of Antwerp, Belgium. In each of these districts, the networks are governed by welfare meetings, defined as a shared participant type of governance. We use exponential random graph models. The results show that a shared participant type of governance has a positive effect on tie formation. We also find that the positive effect on tie formation is dependent on the active participation of centralized actors in the welfare meetings.